Outcomes after Knee Microfracture of Chondral Defects in Alpine Ski Racers - Steadman, J. Richard; Hanson, Chad M.; Briggs, Karen K.; Matheny, Lauren M.; James, Evan W.; Guillet, Alyson (The Journal of Knee Surgery, 2014)
Articular cartilage defects of the knee have been shown to cause pain, swelling, decreased function, and suboptimal athletic performance. Treatment of elite-level athletes presenting with full-thickness chondral defects of the knee continues to be a challenge for orthopedic surgeons. The purpose of this study was to document outcomes in elite professional alpine ski racers after microfracture surgery. This study was approved by an institutional review board. All patients who competed in professional ski races recognized by International Ski Federation and had a full-thickness knee articular cartilage defect, treated with microfracture, by a single surgeon, were included in the study. All data were collected prospectively. At minimum 2 years following microfracture, all patients completed a questionnaire, including Lysholm score, Tegner activity scale, and patient satisfaction with outcome. Minimum 2-year follow-up was available for 18 of 20 skiers (90%) at an average follow-up of 77 months (range, 24–255 months). Size of knee articular cartilage defect was larger in males (195 mm2) compared with females (155 mm2); however, this difference was not statistically significant (p > 0.05). Median postoperative Tegner activity scale was 10 (range, 4–10). Mean postoperative Lysholm score was 86 (range, 41–100). Median postoperative patient satisfaction score was 10 (range, 9–10). Out of the 20 skiers, 19 (95%) returned to competitive skiing. The age of the skier who did not return was 28 years. The average time from surgery to return to competition was 13.4 months (range, 0.5–25.3 months). Average end-of-season overall World Cup ranking was calculated for the nine skiers before and after surgery. Of these nine skiers, six had an improved average overall World Cup ranking after microfracture. In this study, patient satisfaction with outcome and function were high following microfracture of full-thickness chondral lesions of the knee. Nearly all skiers returned to full competition. Microfracture is an acceptable treatment option for elite skiers who have full thickness articular cartilage lesions of the knee.
Keywords: articular cartilage; microfracture; alpine ski racers; outcomes